The environmental impacts of economic development in artisanal fisheries: An analysis from the modes of living and working - Knox, Winifred; Trigueiro, Aline; Zanetti, Daniela (Guará Journal, 2025)
The reflection proposed in this article is based on the experience of academic extension-authors during the development of the project executed in the fishing communities of the coast of Espirito Santo in 2012. Through a dialogic methodology and collecting testimonials (with audiovisual recording), we sought to reflect on the lives and work of these people, mainly regarding the environmental impacts that have suffered due to the expansion of the large economic enterprises in their localities by preventing their reproduction as neglecting social group and their rights
Keywords: Artisanal fishing; Development; Environment; Social rights